Direct Electrodeposition of Molybdenum (VI) from Hydrophobic Ionic Liquids After Solvent Extraction at Room Temperature - Romero-Figueroa, J; Quijada-Maldonado, E (Springer Science and Business Media Deutschland GmbH, 2026)
This work investigates the solvent extraction and direct electrodeposition of molybdenum (Mo) using hydrophobic ionic liquids (ILs) as extractants and diluents, aiming to evaluate their feasibility for Mo recovery at room temperature as a more sustainable alternative to conventional organic systems. The ILs [Ompy][Tf2N] and [Omim][Tf2N] were employed as diluents, while [Toma][Ba] served as the extractant, and their performance was compared with the conventional extractant D2EHPA in kerosene. The results showed that the system [Toma][Ba]/[Ompy][Tf2N] achieved over 98% Mo extraction under acidic conditions and enabled more effective Mo electrodeposition on a glassy carbon electrode. Electrodeposition was carried out at − 1.48 V, yielding Mo deposits in the form of Mo oxide phases (MoOx) without achieving complete reduction to metallic Mo. The process was identified as diffusion controlled and followed a three-dimensional instantaneous nucleation mechanism. The deposit morphology exhibited dendritic structures whose degree of ramification was strongly influenced by the IL composition. The study suggests that ILs enhance electrochemical performance by suppressing hydrogen evolution and enabling the application of a wider electrochemical potential window, which is required for Mo reduction. This work demonstrates the feasibility of using ILs in Mo extraction and recovery by direct electrodeposition, while highlighting the need for further IL design to improve electrodeposition kinetics and advance toward deeper Mo reduction. © The Minerals, Metals & Materials Society 2026.
Keywords: Metal extraction; Electrodeposition; Ionic liquids; Solvent extraction; Molybdenum